Molecular classification of gastric cancer - G. Toni; I. Panarese; R. di Francia; R. Franco (World Cancer Research Journal, 2020)
Gastric cancer (GC) is the third cause of cancer-related death worldwide, with a different distribution, higher among Asians. GC is a multifactorial disease and 90% of cases are sporadic1. Helicobacter pylori is the most common etiological factor, shared with MALT Gastric Lymphoma1,2. Even if iTs incidence is declining, many efforts are focused on new target therapies3. In fact, the prognosis is often poor because GC is almost asymptomatic in the early stages, and the curability is related to the surgical treatment. The Cancer Genome Atlas (TCGA) has proposed a new classification in four subtypes, based on molecular categorization: EBV-positive, Microsatellite-instable (MSI), genomically stable, and chromosomally unstable4–6.